Pengaruh Kualitas Auditor, Audit Tenure, Umur Perusahaan Dan Reputasi Kap Terhadap Ketepatan Waktu Publikasi Pada Perusahaan Manufaktur Sektor Pangan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2020 - Vicky Angelia; Angeline Carolina; Cynthia Cynthia; Arie Pratania (Journal of Economic, Bussines and Accounting (COSTING), 2022)
This study aims to determine and analyze the effect of auditor quality, audit tenure, company age and KAP reputation on the timeliness of publication in food sector manufacturing companies listed on the Indonesia Stock Exchange in 2018 - 2020. The research approach used is a quantitative approach. The sampling method is purposive sampling, a sample of 17 food manufacturing companies listed on the Indonesia Stock Exchange multiplied by 3 years in the study period. The results of the study using multiple linear regression show that auditor quality, audit tenure, company age and KAP reputation have a significant simultaneous effect on the timeliness of publications in food sector manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. Auditor quality has a significant partial effect on the timeliness of publications in food sector manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. Audit tenure has a significant partial effect on the timeliness of publications in food sector manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. Company age does not partially affect the timeliness of publications in food sector manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. KAP reputation does not partially affect the timeliness of publications in food sector manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. Keywords: auditor quality, audit tenure, company age, KAP reputation and timeliness of publication.